VALUE OF MULTICULTURAL ISLAMIC EDUCATIONAT PATRA DHARMA BALIKPAPAN HIGH SCHOOL - Kusnan Kusnan (Journal Education Multicultural of Islamic Society, 2022)
This article aimed to describe value of multicultural islamic educationat patra dharma balikpapan high school . Due to the fact that Patra Dharma Balikpapan High School as an educational institution located in a diverse social environment has an awareness of its responsibility in maintaining togetherness in diversity. This study was conducted as a case study in Senior High School Of Patra Dharma which in practice have instilled the values of multicultural Islamic education. To analyze the event by collecting data through Interview technique, Observation, Documents, Audiovisual And Digital Materials and narrated in the form of qualitative-descriptive with descriptive interpretative analysis. The results of this study indicated therefore diversity must be responded to in the concept of education. For the ability of this goal, it is a value that must be developed, and those values are the values of multicultural Islamic education. These values include; as-samhiyah (tolerance), Al-musawwa (equal rights), tawazzun (equality), and ta'awun (mutual help). The values of multicultural Islamic education are the capital of social values that are crucial in building togetherness in diversity.Keywords: Values of Multicultural, Multicultural Islamic Education, Islamic Education